Civility, Nonviolent Resistance, and the New Struggle for Social Justice - Asfari, Amin, (Value Inquiry Book Series ;, 2020)
In Civility, Nonviolent Resistance, and the New Struggle for Social Justice , Amin Asfari brings together scholarly contributions addressing the causes of injustice in its many forms. Predicated on the idea that violence and injustice are systemic and historical, this collection includes chapters that examine the antecedents and effects of prejudice, state-sponsored violence, policies of exclusion, and the social forces that shape and solidify their existence. Moving beyond ad-hoc, ahistorical, and descriptive explanations of violence and injustice, this volume provides a scholarly, multidisciplinary approach to confronting them. Contributions reflect the many ways in which injustice manifests, and civil, nonviolent means of engagement are emphasized, challenging the very systems that give rise to these notions.